Investigation on the genetic variability of the american pit bull terrier dogs belonging to an italian breeder using microsatellite markers and genealogical data - Ciampolini, R.; Cecchi, F.; Paci, G.; Policardo, C.; Spaterna, A. (Цитология и генетика, 2013)
The genetic variability of 18 American Pit Bull Terriers bred in Italy was studied using 21 STR markers from the panels recommended for the 2006, 2008 and 2010 ISAG canine comparison test and the genealogical information. As expected, all statistical analysis showed a reduced genetic variability. It is there-fore recommended greater attention in the programming of mating with an increase of gene flow among farmers, which would reduce the average inbreeding in the population and increase genetic variability. Генетическая изменчивость 18 американских питбультерьеров, выведенных в Италии, была изучена с использованием 21 STR маркеров из панелей, рекомендованных Международной ассоциацией генетики животных (ISAG canine) (2006, 2008, 2010). Как и ожидалось, все статистические анализы подтвердили невысокую генетическую изменчивость. Поэтому желательно уделять больше внимания пла-нированию скрещиваний с увеличением потока генов, чтобы уменьшить средний инбридинг в популяции и увеличить генетическую изменчивость. Генетична мінливість 18 американських пітбультер’єрів, виведених в Італії, була вивчена з використанням 21 STR маркерів з панелей, рекомендованих Міжнародною асоціацією генетики тварин (ISAG canine) (2006,2008 і 2010). Як і очікувалося, всі статистичні аналізи підтвердили невисоку генетичну мінливість. Тому бажано приділяти більше уваги плануванню схрещувань із збільшенням потоку генів, щоб зменшити середній інбридинг в популяції і збільшити генетичну мінливість.